“Is surgery delayed surgery denied?”- How we managed hepatobiliary pancreatic surgeries among Bangladeshi patients during COVID-19 era - Rabbi, Hashim; Rashid, Md Mamunur; Ahmed, AHM Tanvir; Hakim, HA Nazmul; Chowdhury, Ajmal Quader; Islam, Aminul; Hassan, Md Rafiqul; Imtiaz, Md Shafayet; Sarder, Mahmud Mohammad; Arefin, Mirza Shamsul; Ali, Mohammad (BIRDEM Medical Journal, 2020)
Background: Corona virus disease 2019 (COVID-19) is a disease entity caused by the Severe Acute Respiratory Syndrome coronavirus 2 (SARS COV-2). Although it is not a surgical disease, it significantly influences the management of surgical illness in many ways. Delaying the surgery may be considered as denying the treatment. Authorities all over the world formulated different guidelines and recommendations. Considering current pandemic situation and our patients, we are performing surgeries following our hospital and departmental protocol. Delaying the surgery may negate the treatment and may influence the overall outcome that seem like justice delayed justice denied. Methods: In this prospective observational study, we observed different management approaches to 100 Bangladeshi individuals with hepatobiliary and pancreatic surgical disorders from April 2020 to September 2020, in BIRDEM General Hospital and other hospitals of Dhaka. Patients were thoroughly screened, evaluated and prepared to plan the appropriate management strategy. They were triaged according to presentation and were managed accordingly. Patients consented were only enrolled in this study. Results: The study includes 100 consecutive patients between ages of 21 and 70 years, of them, 77 patients were 4th and 6th decade and only 11 patients (11%) were in 3rd decade of life. Highest 28 patients (28%) were in between 40-49 years and 26 patients in 50-59 years age group. We found 48 patients (48 %) were male and 52 patients (52%) were female. Study showed a slight female predominance and presented at an earlier age than male. The pandemic has created a panic in the society, we were getting less number of patients for HPB surgery in March. Since the end of April 2020 onwards and from July, August and September we have performed 39 surgeries. Conclusion: This article is based on real-time experiences of Hepato-biliary-Pancreatic surgery department of BIRDEM General Hospital and BRB hospitals, Dhaka by the same surgical team. Our experience with COVID-19 positive surgical patients is not gratifying. Modern imaging techniques ensure early detection with better understanding of magnitude of disease, which is essential for proper treatment planning.. Both elective and emergency surgeries can be performed safely with proper precautions. Patients with bridging procedures responded well to planed definitive management. Strategies like neoadjuvant therapy and endotherapies for planned definitive surgical care ensures promising results. Postoperative pneumonia in COVID-19 detected patients is a challenging complication. Optimal management strategy requires a multidisciplinary approach for successful outcome. Birdem Med J 2020; 10, COVID Supplement: 63-70